2020
DOI: 10.1016/j.ncrna.2020.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The significance of microRNA deregulation in colorectal cancer development and the clinical uses as a diagnostic and prognostic biomarker and therapeutic agent

Abstract: Colorectal cancer (CRC) is one of the most widely recognized and deadly malignancies worldwide. Although death rates have declined over the previous decade, mainly because of enhanced screening or potential treatment alternatives, CRC remains the third leading cause of cancer-related mortality globally , with an estimated incidence of over 1 million new cases and approximately 600 000 deaths estimated yearly. Therefore, many scientific efforts are put into the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 160 publications
0
17
0
Order By: Relevance
“…It was shown that Fusobacterium nucleatum -mediated infection induces TLR4/MyDD88, activates NF-κB which binds to miR-21 promoter and increases its transcription [ 51 ]. Oncogenic roles of miR-21 are related to tumor progression, proliferation, EMT, metastasis, invasion, inhibition of apoptosis and induction of stemness [ 179 ]. Moreover, other studies showed KRAS mutations were more frequent in F. nucleatum -infected CRC which is associated with overexpression of miR-21 as well [ 180 ].…”
Section: Diet Gut Microbiota and Their Metabolites Affect Mirnas Expression In Crcmentioning
confidence: 99%
“…It was shown that Fusobacterium nucleatum -mediated infection induces TLR4/MyDD88, activates NF-κB which binds to miR-21 promoter and increases its transcription [ 51 ]. Oncogenic roles of miR-21 are related to tumor progression, proliferation, EMT, metastasis, invasion, inhibition of apoptosis and induction of stemness [ 179 ]. Moreover, other studies showed KRAS mutations were more frequent in F. nucleatum -infected CRC which is associated with overexpression of miR-21 as well [ 180 ].…”
Section: Diet Gut Microbiota and Their Metabolites Affect Mirnas Expression In Crcmentioning
confidence: 99%
“…In recent years, with the continued advancements in molecular biology, signaling pathways and targeted therapy have gradually become the focus of GC research, and are expected to provide more effective means for the treatment of GC (4). The most recent advancements in GC research are in the area of noncoding nucleic acids such as long-non-coding RNAs and miRNAs (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic changes, particularly dysregulated expression levels of miRNAs, can be of prognostic importance (Ahadi, 2020;Chen et al, 2020;Lv et al, 2020) and, therefore, this study was conducted to evaluate such potential of miRNAs, especially with regards to the success of surgery of metastatic bone cancers. Expression of select miRNAs was first analyzed in the bone metastasis of 44 patients with bone metastasis, relative to the adjacent bone material and then I applied this information to evaluate the impact of surgery on outcome of patients by diving the patients into a high risk vs. low risk group based on the miRNA signature.…”
Section: Introductionmentioning
confidence: 99%